Frequency and management of non-obstetric fistula in the Democratic Republic of Congo: experience from Fistula Care Plus project (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the frequency and management of non-obstetric fistula (NOF) in Democratic Republic of Congo (DRC).Methods: A retrospective cohort study reviewed patients’ medical records in three fistula repair sites supported by the USAID-funded Fistula Care Plus (FC+) Project, covering 1 January 2015 to 31 December 2017. Study variables included demographic characteristics, fistula etiology as reported by surgeon, fistula type (Waaldijk classification), and treatment outcomes.Results: Of 1984 women treated for female genital fistula between 2015 and 2017 in the three sites, 384 (19%) were considered to be NOF cases. 91% of these women resided in rural areas. 49.3% were married/in relationship at time of treatment compared to 69% before the fistula (p